Torsion of Hydrosalpinx with Concurrent Acute Cholecystitis: Case Report and Review of Literature - Preeti R. John; Amelia M. Pasley (Case Reports in Surgery)
Introduction. Isolated torsion of the Fallopian tube is an uncommon cause of acute lower abdominal pain and can occur in women of all age groups. Cholecystitis is a frequent cause of upper abdominal pain. We present an unusual case with the presence of these two distinct pathological entities occurring concurrently in the same patient, causing simultaneously occurring symptoms. To our knowledge, this is the first reported presentation of such a case. Methods. We describe a 34-year-old premenopausal woman who presented with right sided upper and lower abdominal pain and nausea. Abdominal ultrasound (US) revealed acute cholecystitis. Vaginal US was suggestive of right hydrosalpinx. Intravenous antibiotics were administered and consent was obtained for operative intervention. During laparoscopy, the right Fallopian tube with hydrosalpinx was noted to be twisted three times. The right ovary appeared normal. The gall bladder wall was thickened and inflamed. Laparoscopic right salpingectomy and cholecystectomy were performed. Results. Surgical pathology revealed hydrosalpinx with torsion and acute calculous cholecystitis. The patient had an uneventful postoperative course and was discharged home on the first postoperative day. Her symptoms resolved after the procedure. Conclusions. In women with abdominal pain, both gynecologic and nongynecologic etiologies should be considered in the differential diagnoses. Concurrent presence of symptomatic gynecologic and nongynecologic intra-abdominal pathology is rare. Isolated Fallopian tube torsion is rare and is associated most often with hydrosalpinx. Some torqued Fallopian tubes can be salvaged. Laparoscopy is useful in management of both Fallopian tube torsion and cholecystitis.